Evolutionary and Developmental Biology Provide Insights Into the Regeneration of Organ of Corti Hair Cells - Elliott, Karen L.; Fritzsch, Bernd; Duncan, Jeremy S. (Frontiers in Cellular Neuroscience, 2018)
We review the evolution and development of organ of Corti hair cells with a focus on their molecular differences from vestibular hair cells. Such information is needed to therapeutically guide organ of Corti hair cell development in flat epithelia and generate the correct arrangement of different hair cell types, orientation of stereocilia, and the delayed loss of the kinocilium that are all essential for hearing, while avoiding driving hair cells towards a vestibular fate. Highlighting the differences from vestibular organs and defining what is known about the regulation of these differences will help focus future research directions toward successful restoration of an organ of Corti following long-term hair cell loss.